Developing Organization using HRM Practices on Employee’s Performance: An Empirical Analysis among Private Bank Employees in Tiruchirappalli - S. Divya; K.R. Chandrakala (International Journal of Engineering and Management Research, 2023)
For retaining the human resources within the organizations, the firms have to encompass their employee force, since the workforce is considered to be the important source for attaining the competitive gain. The aim of the study is to identify the factors related with employee performance that are affected by the practices of HRM through varied dimensions. Further, the study has attempted to propose a model regarding the practices of HR that can be utilized to test and improve the employee performance. Data was collected from the employees working in private banks of Tiruchirappalli. The sample size of the study is 131. Questionnaire is the tool used for collecting responses from the employees. Analysis of the collected responses have been done through SPSS. Respondents have been selected through simple random sampling and analysis has been done through regression. The results of analysis reveal that there exists a strong relationship of HRM practices with the employee performance, with reference to the employees of private banks in Tiruchirappalli.